Quantitative analysis of runoff in green roof structures in the Colorado Front Range - Salerno, Amanda, author; Bousselot, Jennifer, advisor; Choi, Jane, committee member; Sharvelle, Sybil, committee member (Colorado State University. Libraries, 2023)
The green roof capacity of retaining rainwater extends the runoff duration further than the actual rain event, releasing part of it slowly into the drainage system and positively impacting it. However, the volumes will depend on the size of the rainfall event and the green roof design. Therefore, specific attention should be paid when designing a new green roof project, like geographic locations, materials peculiarities, and the project's needs, including biotic and abiotic design components. The need for more local data regarding this analysis in Western North America is still significant. Therefore, this study aims to analyze the impact of three different green roof systems on Colorado's climate by reduction of runoff, retention volume, and runoff coefficient. Moreover, we aim to analyze plant health and substrate moisture retention and components for better water capture. To achieve the goals outlined, three different green roofs technologies, with different retention and detention layers technologies, and a control roof, a conventional low slope roof for comparison, are placed at Colorado State University in Fort Collins, Colorado, United States; the systems include a Sempergreen Purple Roof, a Sempergreen Sponge Roof, and a Green Roof Technology with an Extenduct Drainage System; all were vegetated with Sedum mats, base slopes of 1% toward the rooftop drain, and measuring 1m x 2m. The drainage systems in each green roof were designed to test performance under steady, low-intensity, high-intensity, short-duration, and long-duration rainfall conditions and simulated rain events. All the systems have the same drain system connected to a v-notch weir. Volume, speed, and time were measured to quantify the runoff from all roof systems. Our data suggests that green roof volume capture varies with preexisting substrate moisture conditions, frequency and size of storms, and drainage layer components. Green Roof Technology with an Extenduct Drainage System and Sponge Roof had the best volume retention in less intense, more frequent, and back-to-back rainfall events. On the other hand, Purple Roof performed better for larger rain events that might lead to flooding and urban drainage concerns in cities. Ultimately, the Colorado-specific data from this study will enable the intentional design of green roofs to optimize plant health and water management.